p300/Sp1-Mediated High Expression of p16 Promotes Endothelial Progenitor Cell Senescence Leading to the Occurrence of Chronic Obstructive Pulmonary Disease - Zhihui He; Huaihuai Peng; Min Gao; Guibin Liang; Menghao Zeng; Xuefeng Zhang (Mediators of Inflammation)
Objective. Chronic obstructive pulmonary disease (COPD) is a common chronic disease and develops rapidly into a grave public health problem worldwide. However, what exactly causes the occurrence of COPD remains largely unclear. Here, we are trying to explore whether the high expression of p16 mediated by p300/Sp1 can cause chronic obstructive pulmonary disease through promoting the senescence of endothelial progenitor cells (EPCs). Methods. Peripheral blood EPCs were isolated from nonsmoking non-COPD, smoking non-COPD, and smoking COPD patients. The expressions of p16, p300, and senescence-related genes were detected by RT-PCR and Western Blot. Then, we knocked down or overexpressed Sp1 and p300 and used the ChIP assay to detect the histone H4 acetylation level in the promoter region of p16, CCK8 to detect cell proliferation, flow cytometry to detect the cell cycle, and β-galactosidase staining to count the proportion of senescent cells. Results. The high expression of p16 was found in peripheral blood EPCs of COPD patients; the cigarette smoke extract (CSE) led to the increase of p16. The high expression of p16 in EPCs promoted cell cycle arrest and apoptosis. The CSE-mediated high expression of p16 promoted cell senescence. The expression of p300 was increased in peripheral blood EPCs of COPD patients. Moreover, p300/Sp1 enhanced the histone H4 acetylation level in the promoter region of p16, thereby mediating the senescence of EPCs. And knockdown of p300/Sp1 could rescue CSE-mediated cell senescence. Conclusion. p300/Sp1 enhanced the histone H4 acetylation level in the p16 promoter region to mediate the senescence of EPCs.